PELATIHAN PENGGUNAAN APLIKASI GEOGEBRA UNTUK PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BAGI GURU SMA DI KOTA PAREPARE - Adhalia H, Nurul Fuady; Zaitun, Zaitun; Nisardi, Muh Rifki; Resky, Aprizal; Kusnaeni, Kusnaeni; Husain, Hartina; Tungga, Rifaldy Atlant (Universitas Mataram, 2024)
The The use of technology in the mathematics learning process by high school teachers in the city of Parepare is still lacking. Even though there are many learning media that can be utilized. The Geogebra application is a technological medium that has great potential in integrating mathematical concepts visually and interactively. The aim of implementing this PKM is to provide training to mathematics teachers who are members of MGMP Parepare to develop mathematics learning media at the high school level. The training method used is providing training assistance on the Geogebra application which consists of two stages. The preparation stages consist of observing, coordinating with partners, preparing the service implementation team and preparing the service implementation team regarding the training module. The implementation stages consist of giving a pre-test, providing an explanation regarding the Geogebra application, providing simulation assistance in making mathematics learning media using Geogebra, and providing a post-test. The results obtained from the training showed that 18 out of 20 people or around 90% of teachers were able to understand and apply the knowledge gained in training activities through a post-test given at the end of the activity. Thus, the implementation of the Geogebra Application training activities was considered successful because it had achieved the specified targets.